Social Media Marketing Integration as an Interactive Marketing Strategy To Increase Competitive Advantage - Aprilina, Riska; Wulandari, Astri; Suryawardani, Bethani (CV. Lafadz Jaya, 2026)
This study aims to analyze the role of social media integration as a marketing strategy in optimizing a company's competitive advantage in the digital economy era. The current transformation in marketing strategies has encouraged the integration of digital platforms to foster communication, consumer engagement, and ultimately achieve competitive advantage. The study employed qualitative methods, incorporating literature review of various international and national journals covering digital marketing, social media integration, and competitive advantage. The analysis results indicate increased brand awareness and engagement, optimization of customer relationship management based on real-time data, and increased product and service innovation through consumer feedback. Social media integration enables companies to create a consistent customer experience. Social media integration is not only a marketing communications strategy but also a strategic capability that can support value creation and improve company performance.